2015
DOI: 10.1002/jcb.25053
|View full text |Cite
|
Sign up to set email alerts
|

Fascaplysin Induces Caspase Mediated Crosstalk Between Apoptosis and Autophagy Through the Inhibition of PI3K/AKT/mTOR Signaling Cascade in Human Leukemia HL‐60 Cells

Abstract: In this study, we for the first time explored the cellular and molecular mechanism of anticancer properties of fascaplysin, a marine sponge-derived alkaloid. Our study demonstrated that fascaplysin induced a cooperative interaction between apoptotic and autophagic pathways to induce cytotoxicity in HL-60 cells. Fascaplysin treatment not only activated pro-apoptotic events like PARP-1 cleavage and caspase activation but also triggered autophagy signaling as shown by the increased expression of LC3-II, ATG7and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 38 publications
2
43
0
Order By: Relevance
“…23, 24 Akt and mTOR phosphorylation levels were decreased significantly 2 h after PDT (Figure 5a). Additionally, pre-treatment with the PI3K inhibitor LY294002 or Akt inhibitor triciribine did not affect the expression of p-Akt, p-mTOR and LC3-II (Figure 5b).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…23, 24 Akt and mTOR phosphorylation levels were decreased significantly 2 h after PDT (Figure 5a). Additionally, pre-treatment with the PI3K inhibitor LY294002 or Akt inhibitor triciribine did not affect the expression of p-Akt, p-mTOR and LC3-II (Figure 5b).…”
Section: Resultsmentioning
confidence: 94%
“…The PI3K/Akt/mTOR signaling pathway is a classic autophagy pathway. 23, 24 PI3K and Akt suppression can inhibit mTOR phosphorylation at the Ser 2448 site, thereby enhancing the expression of autophagy-related proteins and inducing autophagy. 37 To determine whether PDT-induced autophagy occurred through the PI3K/Akt/mTOR pathway, we monitored the Akt and mTOR phosphorylation at different time points after PDT and found that mTOR and Akt phosphorylation significantly decreased after PDT.…”
Section: Discussionmentioning
confidence: 99%
“…The marine sponge-derived bis-indole alkaloid Fascaplysin is effective against malaria [1], against bacterial, fungal, and viral infections [1], as well as against malignancy [1][2][3]. The efficacy against malignancy is at least in part due to activation of autophagy and apoptosis of tumor cells [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy against malignancy is at least in part due to activation of autophagy and apoptosis of tumor cells [2,3]. Fascaplysin further counteracts angiogenesis by triggering apoptosis of endothelial cells [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation